Distributional Justice and Efficiency: Integrating Inequality Within and Between Dimensions in Additive Poverty Indices - Nicole Rippin (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
According to Sen (1976), any reasonable poverty index ought to be sensitive to inequality. In a multidimensional framework, inequality between poverty dimensions is traditionally treated as association sensitivity. Such an approach, however, is based exclusively on efficiency considerations, thereby neglecting all aspects of distributive justice. This paper introduces a new property for dealing with inequality that accounts for both efficiency as well as distributive justice. Based on the new property, it then proceeds to derive a new class of inequality-sensitive poverty measures whose advantages are demonstrated by an empirical application to 28 developing countries.
Keywords: I32; 330; Multidimensional poverty measurement; counting indices; inequality; correlation sensitivity; identification